THE IMPACT OF HELMINTH DISEASE: A LITERATURE REVIEW - Muslim, Nurhadi; Hasyim, Hamzah; Nurrobikha, Nurrobikha; Nurhasanah, Nurhasanah; Sari, Nining Indah; Lestari, Ocik; Sari, Nurmaya; Sigalingging, Nurhaida (Jurnal Kesehatan - STIKes Prima Nusantara, 2021)
According to the World Health Organization (WHO), over 1.5 billion individuals, or roughly 24% of the global population, are infected with intestinal worms, which primarily affect school-aged children. India is home to a third of the world's 2.5 billion people without access to proper sanitation, as well as two-thirds of the 11 billion people who practice open defecation and a quarter of the 15 million people who die each year from diarrhoeal diseases. This work does a literature review to investigate the effects of helminthiasis. The articles obtained were extracted and conclusions were drawn from a literature study of intestinal worms using the PubMed database; the number of articles extracted became a conclusion of up to 30 articles, and the strategy for searching for articles in the database used the keywords "disease," "worms," and "worm disease." The impact of gastrointestinal helminth infections on the developing microbiota of juvenile hosts is poorly understood. Four different procedures were employed to determine worm infestation. Anthelmintic resistance (AR) in intestinal helminths of dogs and cats has only been observed on a few occasions, in contrast to parasites of livestock and horses. Soil-transmitted helminths afflict billions of people worldwide, primarily in low- and middle-income countries with inadequate sanitation and high levels of air and water pollution.